Pembuatan Alat Monitoring dan Kontrol Tanaman Cabai berbasis Internet of Things (IoT) - Elgi, Elgi; Fikri, Ryan (Lembaga Yasin AlSys, 2025)
This study is motivated by challenges in chili cultivation, particularly the need for timely irrigation and pesticide spraying, as well as monitoring environmental humidity and temperature, which significantly affect plant productivity. The objective of this research is to design and develop an Internet of Things (IoT)-based monitoring and control system to enhance the efficiency of chili plant care. The system was developed using the Waterfall method, encompassing requirement analysis, design, implementation, and testing stages. Key components include a soil moisture sensor for detecting soil humidity, a DHT11 sensor for measuring air temperature and humidity, and an ESP32 microcontroller integrated with the Blynk application for remote control. Testing results show that the sensors function accurately, with an average temperature measurement error of 0.3%. The automated irrigation system activates when soil moisture falls below a set threshold, and pesticide spraying can be remotely controlled via smartphone. The study concludes that the developed system is effective in supporting precision agriculture practices and contributes to improving the productivity and efficiency of modern chili cultivation.